A new species of Leofa (Prasutagus) Distant (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from Thailand with a checklist of Leofa - Duan, Yani; Zhang, Yalin; Zahniser, James N. (Zootaxa, 2012)
Leofa (Prasutagus) pulla sp. n., is described and illustrated from Thailand. This represents the first record of the genus Leofa Distant from Thailand. A key to known species of the subgenus Prasutagus Distant is provided. A checklist of the genus is provided.